Financial Management Practices and Financial Accounting Standards Compliance: Case of MSMEs in the Northern Philippines - Kristelle Joy C Placido; Kate Corine R Buduan; Vea Neth A de la Cruz; Ynah Bianca E Reynon (International Journal of Entrepreneurship, Business, and Creative Economy, 2024)
Starting a business appeared simple; however, many businesses fail to maintain their operations in the long run. Based on this issue, this study explores the depth of understanding and knowledge of MSME business owners in Ilocos Norte, Philippines, regarding compliance with Financial Accounting Standards (FAS) and Financial Management Practices (FMP). Additionally, it seeks to determine the relationship between FAS and FMP and the success of businesses. The methodology used was a descriptive and correlational design. The data was gathered from 379 MSMEs through a survey questionnaire. A 4-Likert scale was used to analyze and interpret the results. Also, researchers used the International Business Machines Statistical Package for the Social Sciences (IBMSPSS), specifically regression analysis, to correlate the financial performance of the MSMEs to their financial management practices and compliance with the financial accounting standards. The study revealed that micro, small, and medium enterprises (MSMEs) in Ilocos Norte maintain a moderate level of implementation of financial management practices and compliance with financial accounting standards, concentrating on the Statement of Comprehensive Income. The study also revealed a significant relationship between financial management practices, compliance with financial accounting standards, and business performance, leading to success. It is justified that effectively and efficiently managing financial matters can contribute to the enhancement of business performance.